UORFlight: a vehicle toward uORF-mediated translational regulation mechanisms in eukaryotes. (13th March 2020) - Niu, Ruixia; Zhou, Yulu; Zhang, Yu; Mou, Rui; Tang, Zhijuan; Wang, Zhao; Zhou, Guilong; Guo, Sibin; Yuan, Meng; Xu, Guoyong
Abstract: Upstream open reading frames (uORFs) are prevalent in eukaryotic mRNAs. They act as a translational control element for precisely tuning the expression of the downstream major open reading frame (mORF). uORF variation has been clearly associated with several human diseases. In contrast, natural uORF variants in plants have not ever been identified or linked with any phenotypic changes. The paucity of such evidence encouraged us to generate this database-uORFlight (http://uorflight.whu.edu.cn ). It facilitates the exploration of uORF variation among different splicing models of Arabidopsis and rice genes. Most importantly, users can evaluate uORF frequency among different accessions at the population scale and find out the causal single nucleotide polymorphism (SNP) or insertion/deletion (INDEL), which can be associated with phenotypic variation through database mining or simple experiments. Such information will help to make hypothesis of uORF function in plant development or adaption to changing environments on the basis of the cognate mORF function. This database also curates plant uORF relevant literature into distinct groups. To be broadly interesting, our database expands uORF annotation into more species of fungus ( Botrytis cinerea and Saccharomyces cerevisiae ), plant ( Brassica napus, Glycine max, Gossypium raimondii, Medicago truncatula, Solanum lycopersicum, Solanum tuberosum, Triticum aestivum and Zea mays ), metazoan ( Caenorhabditis elegans and Drosophila melanogaster ) and vertebrate ( Homo sapiens, Mus musculus and Danio rerio ). Therefore, uORFlight will light up the runway toward how uORF genetic variation determines phenotypic diversity and advance our understanding of translational control mechanisms in eukaryotes.